2021
DOI: 10.3390/su13031547
|View full text |Cite
|
Sign up to set email alerts
|

Computer Life-Cycle Management System for Avionics Software as a Tool for Supporting the Sustainable Development of Air Transport

Abstract: The article presents selected results of analytical and design works undertaken at the Air Force Institute of Technology (AFIT) in the field of building a computer support and software lifecycle management system that is critical for flight safety. The aim of the work undertaken is to develop methods and carry out verification and testing in order to detect errors in the developed avionics software for compliance with the requirements of the DO-178C standard and its production, certification, and implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Also, this must be concurrent with the system's working and real-time signals [42][43][44]. The diagnostic process should enable a credible assessment of the technical states of all elements making up an ESS [45][46][47]. The surveillance process should also be implemented in the course of a fire hazard-devices operating under adverse environmental conditions.…”
Section: Review Of the Source Literature On Ess Diagnosticsmentioning
confidence: 99%
“…Also, this must be concurrent with the system's working and real-time signals [42][43][44]. The diagnostic process should enable a credible assessment of the technical states of all elements making up an ESS [45][46][47]. The surveillance process should also be implemented in the course of a fire hazard-devices operating under adverse environmental conditions.…”
Section: Review Of the Source Literature On Ess Diagnosticsmentioning
confidence: 99%
“…However, the designers of such important security systems often fail to consider changes in room or building functionality after a long period of operation [1,[85][86][87]. The authors believe that such changes in the intended use of rooms should be reported by the technical supervisors of the facility to the service team of such systems, and this should be reflected modifying, e.g., detectors or detection loops or circuits of the entire FAS [88][89][90]. Modifications to the design should also take into account the functional and power supply reliability (developing a new energy balance) of new FAS devices or elements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Important, reliability-impacting issues that should be taken into account within the FAS operating process are electromagnetic interference [27,45], maximum permissible temperature changes in building rooms with installed detectors [46,47], as well as changes to accelerations, vibrations and shocks in electronic elements [48,49]. In the case of the studies discussed above, individual factors disturbing the FAS operation process were always considered separately.…”
Section: Literature Reviewmentioning
confidence: 99%